2014
DOI: 10.3389/fpls.2014.00361
|View full text |Cite
|
Sign up to set email alerts
|

Structural divergence of plant TCTPs

Abstract: The Translationally Controlled Tumor Protein (TCTP) is a highly conserved protein at the level of sequence, considered to play an essential role in the regulation of growth and development in eukaryotes. However, this function has been inferred from studies in a few model systems, such as mice and mammalian cell lines, Drosophila and Arabidopsis. Thus, the knowledge regarding this protein is far from complete. In the present study bioinformatic analysis showed the presence of one or more TCTP genes per genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Typically, in these papers, a two-letter suffix before 'TCTP' indicates the species, from which the protein sequence was derived (see Gutierrez-Galeano et al (2014) for an example). The yeast orthologue of TCTP was named 'microtubule and mitochondria interacting protein' (Mmi1p) (Rinnerthaler et al 2006), but in another paper, it was also identified as the 'translation-machinery-associated protein 19' (TMA19) (Fleischer et al 2006), and yet the gene symbol in yeast is YKL056c.…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, in these papers, a two-letter suffix before 'TCTP' indicates the species, from which the protein sequence was derived (see Gutierrez-Galeano et al (2014) for an example). The yeast orthologue of TCTP was named 'microtubule and mitochondria interacting protein' (Mmi1p) (Rinnerthaler et al 2006), but in another paper, it was also identified as the 'translation-machinery-associated protein 19' (TMA19) (Fleischer et al 2006), and yet the gene symbol in yeast is YKL056c.…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
“…Secondary structure elements are highlighted as follows: magenta: α-helices, yellow: β-sheets, blue lines: unstructured areas; major domains are indicated (from : Feng et al 2007a, PDB ID: 2HR9) A considerable number of 3D structures of other members of the TCTP family, in particular from various plant species, have been predicted (Gutierrez-Galeano et al 2014;Hinojosa-Moya et al 2008;Berkowitz et al 2008), based on the experimentally determined 3D-structures of TCTP and on sequence comparisons. Phylogenetic comparisons showed that the predicted tertiary structure of TCTP proteins is in general highly conserved throughout evolution (Gutierrez-Galeano et al 2014;Hinojosa-Moya et al 2008), although there are some deviations in the TCTP structure of lower eukaryotes (Hinojosa-Moya et al 2008) and some species of chlorophyta do not seem to have a TCTP gene at all (Gutierrez-Galeano et al 2014). In the plant kingdom, two principal types of TCTP structures are being distinguished, with some plants having the gene for one of the two types, whereas other ones have genes for both types (Gutierrez-Galeano et al 2014).…”
Section: Molecular Structure Conservation and Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to mammalian TCTPs, plant TCTPs play important roles in cell growth, development, and anti-stress responses (Gutierrez-Galeano et al 2014). It has also been proposed that plant TCTP has functions specific to plant, such as the participation of photoperiodism, flowering, and auxin homeostasis (Gutierrez-Galeano et al 2014).…”
mentioning
confidence: 99%
“…only a few of works have been reported about the function of TCTP in plants ( Gutierrez-Galeano et al 2014). Similar to mammalian TCTPs, plant TCTPs play important roles in cell growth, development, and anti-stress responses (Gutierrez-Galeano et al 2014).…”
mentioning
confidence: 99%